The Framing of Myth in the Creation of a Palestinian Identity: Hamas, Fatah and Children’s Media - Blank, Alyssa S. (Université d'Ottawa / University of Ottawa, 2011)
This thesis is an exploratory examination of identity construction and children’s media, with a focus on the Palestinian political groups of Fatah and Hamas. It looks at how children’s media are framed within the context of the Arab-Israeli conflict. It examines how internal and external social factors contribute to identity formation and the interaction among these elements during times of conflict and war. This thesis hypothesizes that both Fatah and Hamas use various myths to differing degrees in order to frame their conception of a Palestinian identity. Specifically, it explores the use of the Myth of Battle, the Myth of Hero, the Myth of Victim, the Myth of Religion, the Myth of Land and the Myth of Other. It seeks to determine which of these myths each group emphasizes through a qualitative and quantitative visual ethnographic content analysis. The quantitative analysis uncovered interesting, albeit not statistically significant, differences between Fatah’s and Hamas’ use of all of the myths in their videos. Specifically it found that both groups made equal and great use of the Myth of Religion; that Hamas produced the videos with the greatest focus on the Myth of Battle and the Myth of Hero; and that neither group greatly emphasized the Myth of Victim, the Myth of Land or the Myth of Other. Finally, the analysis discovered positive correlations between the Myth of Hero and the Myth of Battle as well as between the Myth of Battle and the Myth of Other.
Keywords: Identity; Myth; Palestinian Discourse; Hamas; Fatah; Children's Media